2023
DOI: 10.1021/acsnano.2c10251
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Frameworks (MOF)-Assisted Sonodynamic Therapy in Anticancer Applications

Abstract: Sonodynamic therapy (SDT) has emerged as a promising therapeutic modality for anticancer treatments and is becoming a cutting-edge interdisciplinary research field. This review starts with the latest developments of SDT and provides a brief comprehensive discussion on ultrasonic cavitation, sonodynamic effect, and sonosensitizers in order to popularize the basic principles and probable mechanisms of SDT. Then the recent progress of MOF-based sonosensitizers is overviewed, and the preparation methods and proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 222 publications
0
42
0
Order By: Relevance
“…95,96 In a typical SDT process, nanolevel transient pores are formed on the cell membrane, which can improve the permeability of tissues. 97 Importantly, US exhibits satisfying tissue penetrability and biological safety, which supports the potential application of SDT. Actually, ultrasound irradiation has been employed as an ideal tool for clinical cancer imaging treatment.…”
Section: Sonodynamic Therapymentioning
confidence: 78%
See 2 more Smart Citations
“…95,96 In a typical SDT process, nanolevel transient pores are formed on the cell membrane, which can improve the permeability of tissues. 97 Importantly, US exhibits satisfying tissue penetrability and biological safety, which supports the potential application of SDT. Actually, ultrasound irradiation has been employed as an ideal tool for clinical cancer imaging treatment.…”
Section: Sonodynamic Therapymentioning
confidence: 78%
“…In order to avoid the rapid degradation of organic sonosensitizers, encapsulating these molecules into the pore of MOFs is a simple and feasible method. 97 Huang et al developed a Cu-MOF with Cu ion and azobenzene 4,4-dicarboxylic acid ligand and encapsulated 2,2-azobis[2-(2-imidazolin-2-yl) propane] dihydrochloride (AIPH) into the Cu-MOF (Fig. S7a).…”
Section: Dynamic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the inherent shortcomings of photosensitizers, such as long-term skin sensitivity, low bioavailability, and poor stability, cannot be avoided, which limits the use of organic sonosensitizers in practical practice. [81][82][83][84][85] Inorganic sonosensitizers include titanium dioxide (TiO 2 ), zinc oxide (ZnO 2 ), black phosphorus (BP), Bi 2 MoO 6 , MnWO x , and so on. In many previous studies, inorganic sonosensitizers have been found to have superior physical and chemical properties and high stability and can provide more nucleation sites for cavitation bubbles by ultrasonic stimulation, resulting in continuous ROS generation.…”
Section: Sonosensitizersmentioning
confidence: 99%
“…In addition, we review sonocatalysis and sonodynamic therapy (SDT) using emerging porous solids as sonosensitizers (Scheme 1). While a limited number of reviews that discuss MOF sonosynthesis 8 and SDT using MOFs from biological and therapeutic perspectives have appeared, 20,21 no comprehensive review that covers sonosynthesis, sonocatalysis, and SDT from the porousmaterial perspective appears to exist. In particular, this is the first review that explores the use of sonochemistry in COF and POP applications, as previous reviews only focused on MOFs.…”
Section: Introductionmentioning
confidence: 99%